ANALISIS OPTIMASI BIAYA KONSTRUKSI KOLOM DENGAN VARIASI NILAI ? DAN fc' - Gerry Revaldo Gerry Revaldo; Fepy Supriani; Mukhlis Islam (Inersia: Jurnal Teknik Sipil, 2019)
This research aims to study the most optimum and economical of square reinforced concrete column with the variation of ? and fc'. Process optimization in this study requires repetitive calculations by using a Microsoft Office Excel. Analysis of the cost of construction of reinforced concrete columns square cross-section consists of 840 samples with variation of column section dimensions, compressive strengths of concrete (fc'), nominal axial capacity of columns (Pn), and nominal bending moment capacity of column (Mn). The results of the sample analysis are interaction charts corresponding column dimension and cost and interaction of fc' and cost consisting of 1,152 charts and also produces composite charts from the previous chart, which is the interaction, among dimension, fc', and cost of column consists of 96 graphs with variation column without using formwork, formwork 1 time use, of formwork used 2 times, 3 times and use disposable formwork. Hence from all of the cost of the optimum structure of the column with the variation of the Mn and Pn of could be concluded that the greater the value of Mn while Pn constant the of value of ?, column dimensions, and cost structure would dominantly increase and it could be concluded also that the greater the value of Pn with constant Mn value then the value of ? and the cost structure would dominantly decrease while the dimensions have not changed and the compressive strength of concrete (fc') used are 25 MPa - 30 MPa.